Effect of Almond Consumption on Metabolic Risk Factors—Glucose Metabolism, Hyperinsulinemia, Selected Markers of Inflammation: A Randomized Controlled Trial in Adolescents and Young Adults - Madan, Jagmeet; Desai, Sharvari; Moitra, Panchali; Salis, Sheryl; Agashe, Shubhada; Battalwar, Rekha; Mehta, Anushree; Kamble, Rachana; Kalita, Soumik; Phatak, Ajay Gajanan; Udipi, Shobha A.; Vaidya, Rama A.; et al. (Frontiers in Nutrition, 2021)
A large percentage of Indian population has diabetes or is at risk of pre-diabetes. Almond consumption has shown benefits on cardio metabolic risk factors in adults. This study explored the effect of almond consumption on determinants of metabolic dysfunction - blood glucose, lipids, insulin and selected inflammatory markers in adolescents and young adults aged 16-25 years from Mumbai city. This cluster randomized trial was conducted for 90 days on individuals with impaired levels of glucose (fasting glucose (5.6-6.9mmol/L), 2h post-glucose (7.8-11.0mmol/L) and /or insulin (fasting insulin (≥15mIU/ ml) /stimulated insulin (≥80mIU/ml). 421 individuals were selected after screening 1313 individuals. The trial was registered with Clinical Trials Registry India (CTRI) CTRI/2018/02/011927(http://ctri.nic.in/Clinicaltrials/showallp.php?mid1=22407&EncHid=&userName=CTRI/2018/02/011927). The almonds group (n=107) consumed 56g almonds daily, the control group (n=112) was given an iso-caloric snack. At baseline and endline, blood glucose, insulin, HbA1c, LDL-c, HDL-c, total, ox- cholesterol, triglycerides, hs-CRP, IL-6, TNF-α, adiponectin, leptin were measured HOMA-IR and FG:FI ratios were calculated. Dietary intakes were assessed. Baseline values for all measurements, macronutrient intakes did not differ significantly between the two groups. Almond consumption significantly decreased HbA1c, total cholesterol, LDL-c. Stimulated insulin decreased post-intervention in both groups, but was greater in almonds group. FG:FI ratio decreased in almonds group. TNF-α and IL-6 decreased in almonds group, while it increased in control group. Our results showed that almonds reduced HbA1c, LDL-C and total cholesterol levels in just 12 weeks of consumption in these adolescents and young adults who were at risk for developing diabetes. Almonds can be considered as one of the food-based strategies for preventing pre-diabetes.